Fanzines, transgressão e existência! Discussões sobre lesbianidades no ensino de história a partir da produção escrita de Vange Leonel entre 1997-2011 - Silva, Ana Carolina do Carmo (2025)
This work aims to promote a pluralistic historical narrative that makes lesbian existences visible, by addressing the representation of lesbianism in the teaching of History. It focuses on the life trajectory and written works of Vange Leonel, produced between 1997 and 2011. Additionally, the research seeks to challenge culturally naturalized discourses on sexuality and lesbianism, moving beyond a strictly disciplinary approach—though without disregarding it—by incorporating perspectives that encompass feelings, affections, desires, pleasures, and the political dimension. As a propositional element, the study includes the creation of a collection of thematic fanzines designed to foster reflection, discussion, and contextualization of lesbianism, highlighting both its continuities and discontinuities.